Reading the ‘Signs of the Time’: Just War Statecraft and the ‘Immorality’ of Nuclear Weapons - Braun, Christian Nikolaus (Studies in Christian ethics, 2024)
This article grapples with the justifiability of nuclear deterrence in the aftermath of Russia's war of aggression against Ukraine. Disillusioned about the failed promise of nuclear disarmament, as well as other ethical issues inherent to nuclear weapons, Pope Francis has attached the immorality label not just to the use of the Bomb but also to its very possession. This step, which his predecessors hesitated to take during the Cold War and the quarter of a century after the fall of the Berlin Wall, has received considerable attention. However, these assessments precede the war against Ukraine. Given that the regime of Vladimir Putin has repeatedly made nuclear threats in the context of this war, and a Cold War 2.0 of sorts has returned, there is reason to reappraise Francis's argument on nuclear weapons for a post-2022 era. I argue with regret that in light of the contemporary security environment it would be a sign of irresponsible statecraft to abandon the nuclear deterrent unilaterally. At the same time, I hold that a renewed and genuine effort needs to be made not just to avoid nuclear war but to create a culture that one day will lead to complete nuclear disarmament.